Perceptions of food waste reduction in Sri Lanka’s commercial capital, Colombo - Reitemeier, Maren; Aheeyar, Mohamed M. M.; Drechsel, Pay (MDPI, 2021)
In 2019, Sri Lanka introduced two policies that referred to food waste and the need to reduce it. To understand key stakeholders’ readiness in this context, this study analyzed the food waste perceptions of private and public sectors in Colombo (open markets, supermarkets, hotels, restaurants, canteens, food caterers and key authorities). Interviews were carried out with operational managers and public officials, as well as other stakeholders who have roles in food waste redistribution and reuse, such as NGOs and the livestock sector. So far, the food-waste-related policy recommendations lack an operational inter-institutional home which can build on measures, like standards, regulations and incentives. Thus, most food waste reduction initiatives are initiated by NGOs or by the private sector, e.g., by larger hotels and supermarket chains. These entities were ready to lead by example, based on the understanding that urban food waste is an internal (financial) management challenge. Among smaller local entities, food waste was perceived more as an external issue to be handled by the city’s waste collection services. Although perceptions varied between entities generating smaller or larger quantities of food waste, there was general agreement that suboptimal capacities and mechanisms to quantify, monitor and cost food waste generation appeared to be obstacles for in-depth awareness creation and action. There was significant interest in communication platforms for cross-sectoral learning, win/win collaborations with reliable collection (reuse) services that are currently operational, such as those provided by piggeries, as well as surplus redistribution initiatives if food safety and related liabilities can be addressed effectively.